Control over the Personal Archive: Reinterpreting the 'Right to be Forgotten' through the Perspective of Foucault's Discourse - Fachmi, Achmad; Setiawan, Agung; Nurfitria, Adista (Inkunabula: Journal of Library Science and Islamic Information, 2025)
Personal archives not only serve an administrative function, but also contain memories, identities, and agencies closely related to human rights. Therefore, personal archives give individuals control over whether they want to be remembered or forgotten, because not everyone wants to be part of the collective memory. So, the Right to be Forgotten (RtbF) exists as the individual's Right to delete their personal information and as a form of antithesis to archival management, while challenging the dominance of the narrative of archival institutions as epistemic and controlling authorities of collective memory. This study aims to reinterpret RtbF through the lens of Foucault's discourse to reveal the relationship between knowledge and power in the context of personal archive management practices. In this study, Foucault's discourse analysis is used to illustrate how the RtbF principle provides data subjects with a space of control over their personal archives. The results of the study show that RtbF serves as both a legal instrument and an ethical discourse that disrupts the hegemony of archival institutions while strengthening individual autonomy as data subjects. This concept emphasizes that personal archives are not merely repositories of information, but also representations of private rights that must be protected within the framework of personal data protection. This study emphasizes the importance of harmonizing RtbF with archival activities and argues that a design policy is needed to accommodate individuals' rights over their personal data in archival activities. Abstrak Arsip personal tidak hanya berfungsi administratif, tetapi juga memuat memori, identitas, dan agensi yang berkaitan erat dengan hak asasi manusia. Oleh karena itu, arsip personal memberi individu kendali untuk menentukan apakah dirinya ingin diingat atau dilupakan. Karena tidak semua individu mau diingat dan menjadi memori kolektif. Sehingga konsep hak untuk dilupakan. Sehingga prinsip Right to be Forgotten (RtbF) hadir sebagai hak individu untuk menghapus informasi pribadinya dan sebagai bentuk antitesis dari pengelolaan arsip, sekaligus menantang dominasi narasi lembaga kearsipan sebagai episteme dan pengendali memori kolektif. Penelitian ini bertujuan mereinterpretasi RtbF melalui perspektif wacana Foucault guna mengungkap relasi pengetahuan dan kekuasaan dalam praktik pengelolaan arsip personal. Pendekatan analisis wacana Foucault digunakan untuk mendeskripsikan bagaimana prinsip RtbF memberi ruang kontrol bagi subjek data atas arsip pribadinya. Hasil kajian menunjukkan bahwa RtbF menjadi instrumen hukum sekaligus diskursus etis yang mendisrupsi hegemoni lembaga kearsipan, sekaligus memperkuat otonomi individu sebagai subjek data. Konsep ini menegaskan bahwa arsip personal bukan sekadar objek informasi, melainkan representasi hak privat yang harus dilindungi dalam kerangka pelindungan data pribadi. Penelitian ini menekankan pentingnya harmonisasi RtbF dengan kegiatan kearsipan, sehingga diperlukannya desain kebijakan yang mampu mengakomodasi hak-hak individu atas data pribadinya dalam kegiatan kearsipan.